Pengaruh Latihan Power Tungkai terhadap Kemampuan Tendangan Dollyo dalam Cabang Olahraga Taekwondo pada Atlet SKTC Dojang Sea - Mieke Mumekh; Jeanne Malonda; Claudia Triana Rorimpandey (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2024)
The problem in this study is whether there is an effect of leg power training on dollyo's kicking ability in taekwondo in SKTC Dojang Sea athletes. The purpose of the study was to determine the extent of the effect of leg power training on dollyo's kicking ability in taekwondo in SKTC Dojang Sea athletes. The research hypothesis of agility training is the influence of limb power training on dollyo's kicking ability in taekwondo. The research method used is the experimental method. The population in this study was all SKTC Dojang Sea athletes totaling 16 athletes, the sample was the entire population divided into two groups, namely 8 experimental group athletes and 8 control group athletes. The data collection instrument "dollyo kick test" technique is one athlete holding a punching bag and the other taking turns kicking using the Dollyo kick technique to the target provided for 30 seconds. The way to score is by calculating the amount of explosive power of kicks made by test participants. The research design used: randomized control groups pre-tast and post-test design. Hypothesis testing using statistical techniques with t test. The results of hypothesis analysis, obtained t observation worth 13,256 while t table obtained from degrees of freedom n1 + n2 - 2 is 8 + 8 - 2 = 14 and confidence level = 0.05 is 2.145. In accordance with the test criteria, accept Ho if the observation t is smaller than the table t, and reject Ho if the observation t is greater than the table t. Because t observation is greater than t in the table, the results of the analysis show reject Ho and accept Ha. Research conclusion: From the results of research that has been proven by training and data analysis objectives based on the variables measured, a conclusion can be drawn that there is an increase in dollyo kicking ability in taekwondo in SKTC Dojang Sea athletes.